2008
DOI: 10.1016/j.jacc.2007.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Longer Repolarization in the Epicardium at the Right Ventricular Outflow Tract Causes Type 1 Electrocardiogram in Patients With Brugada Syndrome

Abstract: Our data provide support for the hypothesis that the negative T-wave associated with type 1 BrS ECG is due to a preferential prolongation of the epicardial AP secondary to accentuation of the AP notch in the region of the right ventricular outflow tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 29 publications
(21 reference statements)
3
57
2
Order By: Relevance
“…Still, electrograms in proximity to the epicardial RVOT have been recorded simultaneously with endocardial RVOT electrograms in BrS patients with the use of a guide wire in the conus branch. 31 That study showed that ARI and RT were longer at RVOT epicardium than at RVOT endocardium after pilsicainide administration and that a delay in AT occurred. Although this method also has its limitations, it would have been valuable to study electrograms in this RV region.…”
Section: Limitationsmentioning
confidence: 91%
“…Still, electrograms in proximity to the epicardial RVOT have been recorded simultaneously with endocardial RVOT electrograms in BrS patients with the use of a guide wire in the conus branch. 31 That study showed that ARI and RT were longer at RVOT epicardium than at RVOT endocardium after pilsicainide administration and that a delay in AT occurred. Although this method also has its limitations, it would have been valuable to study electrograms in this RV region.…”
Section: Limitationsmentioning
confidence: 91%
“…In 2 studies, unipolar electrograms from the epicardium of the right ventricular outflow tract demonstrated no early repolarization during the ST-segment. 39,40 Similarly, monophasic action potentials recorded at the right ventricular epicardium during open heart surgery demonstrated no loss of dome or early repolarization. 41 Also, arrhythmias appeared to originate from the subendocardium rather than from the subepicardium during a mapping study.…”
Section: Limitations To the Concept Of The Brugada Syndrome As A Chanmentioning
confidence: 95%
“…This discriminating electrophysiologic mechanism is thought to be associated with ST-segment elevation (J wave) and T-wave inversion in this syndrome. In a human study using the activation recovery interval (ARI) method, Nagase et al demonstrated that the inverted T wave associated with the type 1 ECG is due to a preferential epicardial ARI prolongation secondary to accentuation of the action potential notch in the right ventricular outflow tract, 14 consistent with the results of the experimental study. The data obtained in previous studies support the results of the present study.…”
Section: Article P 844mentioning
confidence: 58%